Developing problem-based learning comic to enhance mathematical literacy skills for elementary students - Wirda Hayatina Lubis; E. Elvis Napitupulu; Kms Muhammad Amin Fauzi (Inovasi Kurikulum, 2025)
The lack of mathematical literacy among primary school students, especially in understanding and interpreting data, highlights the need for contextual and visual learning media to support mathematical thinking. This study aims to develop a comic-based learning media using the Problem-Based Learning (PBL) model to enhance students' mathematical literacy on data presentation. The development process adopts the ADDIE model, including analysis, design, development, implementation, and evaluation stages. The analysis stage identifies students' needs, followed by the design stage, which involves developing storyboards and comic visualizations using Canva. The comic was validated by subject matter, media, and language experts. The subjects were III-grade students and teachers at SD Negeri 058374 Sei Limbat. Data collection instruments included validation sheets, practicality questionnaires, and mathematical literacy tests. The validation demonstrated high feasibility in terms of content, visual design, and language. Practicality was reflected in the ease of use and student engagement. Effectiveness was measured using a pretest and a posttest, with a gain score analysis. This study confirmed that PBL-based comic media is valid, practical, and effective in improving students’ mathematical literacy in data presentation, supporting critical thinking and problem-solving skills in a contextual learning environment.   Abstrak Rendahnya kemampuan literasi Matematika di kalangan peserta didik sekolah dasar, dalam memahami dan menafsirkan data, menunjukkan pentingnya media pembelajaran kontekstual dan visual untuk mendukung pemikiran matematis. Penelitian ini bertujuan untuk mengembangkan media pembelajaran berbasis komik menggunakan model Problem-Based Learning (PBL) guna meningkatkan literasi Matematika peserta didik dalam penyajian data. Proses pengembangan mengadopsi model ADDIE, yang meliputi tahap analisis, desain, pengembangan, implementasi, dan evaluasi. Tahap analisis mengidentifikasi kebutuhan peserta didik, diikuti dengan tahap desain yang melibatkan pengembangan storyboard dan visualisasi komik menggunakan Canva. Komik tersebut diverifikasi oleh ahli materi pelajaran, media, dan bahasa. Subjek penelitian adalah peserta didik kelas III dan guru di SD Negeri 058374 Sei Limbat. Alat pengumpulan data meliputi lembar verifikasi, kuesioner kepraktisan, dan tes literasi Matematika. Validasi menunjukkan tingkat kelayakan yang tinggi dalam konten, desain visual, dan bahasa. Praktisitas tercermin dalam kemudahan penggunaan dan keterlibatan peserta didik. Efektivitas diukur menggunakan pretest dan posttest, dengan analisis skor gain. Studi ini membuktikan bahwa media komik berbasis PBL valid, praktis, dan efektif dalam meningkatkan literasi Matematika peserta didik dalam penyajian data, serta mendukung keterampilan berpikir kritis dan pemecahan masalah dalam lingkungan belajar kontekstual. Kata Kunci: literasi Matematika; media komik; problem-based learning; sekolah dasar